Witchcraft and Poverty in Africa: A Pastoral Perspective - Kakwata, Frederick (Black theology, 2018)
The issue of witchcraft and its relationship to poverty in Africa is often neglected or only hinted at in the literature on development. However, witchcraft is recognised as having a significant impact on African society. In this article the researcher explores observations and experiences, from the perspective of pastoral care, in terms of the support or refutation of the view that witchcraft is one of the causes of poverty. The data in this qualitative study derive from interviews conducted with 25 pastors in Congo Evangelistic Mission (CEM) in the city of Lubumbashi. The findings indicate that, witchcraft is a lived reality in Congo as well as in Africa, and certain people fall into poverty as a result of the oppressive forces of witchcraft. The article concludes that if poverty is to be addressed holistically, all dimensions of poverty including the spiritual aspect (in this case witchcraft) have to be taken into consideration.